2022
DOI: 10.1021/acsanm.2c02819
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Tuning Resonance Raman Scattering in Monolayer, Trilayer, and Many-Layer Molybdenum Disulfide

Abstract: We report a pressure-dependent resonance Raman study of mechanically exfoliated one-layer (1L), three-layer (3L), and many-layer MoS2 near the A excitonic transitions by using an excitation energy of 1.96 eV. Our results show a linear blue shift for the majority of phonon modes, except for the second-order phonons LA­(K) + TA­(K) and 2LA, whose pressure-dependent frequency is non-linear. The pressure dependence of these bands is explained by considering the dispersive scattering process that gives rise to thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…18,22,45,46 More recent works, however, exhibit a phonon hardening of all Raman modes for MoS 2 and WSe 2 when subjected to high pressures. 47,48 In 2016, M. S. Kim et al, 49 when studying dry transferred TMDs, observed some small Raman shifts of the first order bands and related them to electron doping in MoS 2 and hole doping in MoSe 2 resulting from charge transfer. Nevertheless, when MoS 2 is submitted to electron gate doping, one observes that there is a downshift of the out-of-plane A′ 1 mode, together with an increase of its fwhm, while the E′ mode does not change, which is explained because of the weaker electron−phonon coupling of the in-plane mode.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…18,22,45,46 More recent works, however, exhibit a phonon hardening of all Raman modes for MoS 2 and WSe 2 when subjected to high pressures. 47,48 In 2016, M. S. Kim et al, 49 when studying dry transferred TMDs, observed some small Raman shifts of the first order bands and related them to electron doping in MoS 2 and hole doping in MoSe 2 resulting from charge transfer. Nevertheless, when MoS 2 is submitted to electron gate doping, one observes that there is a downshift of the out-of-plane A′ 1 mode, together with an increase of its fwhm, while the E′ mode does not change, which is explained because of the weaker electron−phonon coupling of the in-plane mode.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Figure 2 compares the Raman spectrum of the synthesized MoS2 layers with the bulk state. The bulk sample includes two peaks, E 1 2g and A1g, which are in the range of 381 cm -1 and 408 cm -1 [10]. But these peaks have shifted to positions of 385 cm -1 and 405 cm -1 for MoS2 layers, respectively, which confirms that they are multi-layered [11].…”
Section: Resultsmentioning
confidence: 87%